Changes in the development of opioid tolerance on re-exposure among people who use heroin: A qualitative study. - Joanna May Kesten; Ed Holder; Rachel Ayres; Pete Ellis; Steve Taylor; Matthew Hickman; Graeme Henderson (PLoS ONE, 2022)
Background and aims This qualitative study aimed to explore how the development of tolerance to both the psychoactive and respiratory depressant effects of heroin on re-exposure are experienced by people who use heroin. Methods Semi-structured one-to-one interviews were conducted with 20 adults who currently or previously used heroin (for at least 6 months), with any type of administration (injected, smoked) and experience of abstinence (at least 2 weeks) and relapse. Topic guides explored the participants understanding of tolerance, their experience of developing tolerance to heroin and of tolerance following relapse. Interviews were audio-recorded and transcribed. Thematic analysis was used to generate salient themes. Results The analysis produced three broad themes: lay understanding of tolerance; tolerating tolerance; and rapid tolerance development following relapse. Tolerance was defined as the body adapting to regular drug use, so that the drug no longer produced the same level of effect. Tolerance was experienced as interacting and co-developing with physical dependence and the symptoms of withdrawal. Indeed, several participants did not differentiate between tolerance and dependence. Most participants did not notice tolerance to respiratory depression. Tolerance levels fluctuated-increasing over periods of regular use and reducing when abstinent. Using more drug was the most common response to increasing tolerance to the desired effects. On re-use following abstinence, tolerance was experienced as developing more quickly in the most recent relapse compared to the first. Tolerance was also perceived to return more quickly with each abstinence-relapse cycle. Conclusions Qualitative accounts of tolerance report that tolerance returns more quickly with each relapse episode. By elucidating the mechanism(s) involved and potentially discovering how they could be switched on prior to relapse occurring we might be able to develop a beneficial harm reduction treatment for people in abstinence that would protect against overdose occurring on subsequent relapse.